2021
DOI: 10.1186/s13584-021-00444-2
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to completing colonoscopy after a positive fecal occult blood test

Abstract: Background Colorectal cancer leads to significant morbidity and mortality. Early detection and treatment are essential. Screening using fecal occult blood tests has increased significantly, but adherence to colonoscopy follow-up is suboptimal, increasing CRC mortality risk. The aim of this study was to identify barriers to colonoscopy following a positive FOBT at the level of the patient, physician, organization and policymakers. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 41 publications
0
10
0
1
Order By: Relevance
“…Recommendation by a physician is the strongest factor motivating people to go for screening in the opportunistic setting 151 152. As for the compliance to follow-up procedures after a positive FIT, lack of comprehension about the test was the strongest predictor of non-adherence, whereas higher socioeconomic status, higher perceived threat, higher cues for action, lower perceived barriers, and higher health behaviour scores were identified as factors associated with a greater willingness to undergo diagnostic colonoscopy after a positive FIT 153 154. Individual programmes should increase efforts to remove or overcome those barriers to follow-up colonoscopy, thereby maximising the effectiveness of the screening.…”
Section: Resultsmentioning
confidence: 99%
“…Recommendation by a physician is the strongest factor motivating people to go for screening in the opportunistic setting 151 152. As for the compliance to follow-up procedures after a positive FIT, lack of comprehension about the test was the strongest predictor of non-adherence, whereas higher socioeconomic status, higher perceived threat, higher cues for action, lower perceived barriers, and higher health behaviour scores were identified as factors associated with a greater willingness to undergo diagnostic colonoscopy after a positive FIT 153 154. Individual programmes should increase efforts to remove or overcome those barriers to follow-up colonoscopy, thereby maximising the effectiveness of the screening.…”
Section: Resultsmentioning
confidence: 99%
“…Awareness about how mixed-methods approaches could help improve follow-up colonoscopy is increasing ( Azulay et al, 2021 , Bertels et al, 2022 , Selby et al, 2019 ). In an Israeli population, Azulay et al found in telephone surveys (quantitative) that lack of comprehension regarding test completion, the abnormal result, and subsequent recommendations were the strongest predictors for lack of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…In an Israeli population, Azulay et al found in telephone surveys (quantitative) that lack of comprehension regarding test completion, the abnormal result, and subsequent recommendations were the strongest predictors for lack of follow-up. In their qualitative analysis (focus groups and in-depth interviews), the authors found that lack of test results awareness and physician workload, were the most frequently reported reasons for lack of follow-up colonoscopy ( Azulay et al, 2021 ). These results differ from our study where the most common EHR documented (quantitative) barrier to follow-up colonoscopy was patient declining the procedure and the most common patient-reported (qualitative) barrier was fear of the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, adherence to colonoscopy was intensely researched among patients who had positive FOBT and there are several reasons for barriers to endoscopic follow-up, including the four main groups: information technology (IT) [ 19 , 20 ], healthcare organizations [ 21 , 22 ], physician behavior [ 23 , 24 , 25 , 26 ], and patient emotional and cognitive factors [ 27 , 28 , 29 , 30 ]. In addition, barriers could affect adherence to colonoscopy and the barriers could be related to the patients, providers, and system barriers [ 31 ].…”
Section: Discussionmentioning
confidence: 99%